Dampak Paparan Asap Rokok (Secondhand Smoke) terhadap Kejadian Bronkopneumonia pada Balita: Sebuah Laporan Kasus - Ahmad Fathin Al Farisi; Shinta Nareswari (CV. Jasa Sukses Abadi, 2026)
Bronchopneumonia is a lower respiratory tract infection that remains a major cause of morbidity and mortality among children, particularly toddlers. Exposure to environmental tobacco smoke has been recognized as an important risk factor that increases children's susceptibility to respiratory infections. This case report aims to describe the impact of secondhand smoke exposure on the occurrence of bronchopneumonia in a toddler. A 1.5-year-old boy presented with a six-day history of productive cough with thick green sputum, shortness of breath, and fever. The diagnosis was established based on medical history, physical examination such as takipneu and subcostal retraction, laboratory investigations, and chest radiography, which revealed bilateral patchy perihilar infiltrates. Exposure to cigarette smoke from his father, an active smoker, was identified as the primary risk factor. Management consisted of intravenous Ringer’s lactate fluid therapy, intravenous ampicillin, and oral paracetamol. After five days of treatment, the patient demonstrated significant clinical improvement and was discharged for outpatient follow-up. Secondhand smoke exposure is thought to contribute to the pathogenesis of bronchopneumonia by impairing mucociliary clearance, increasing mucus production, and suppressing local immune responses, thereby facilitating bacterial colonization of the lower respiratory tract. This case highlights that the harmful effects of cigarette smoke exposure may outweigh the protective benefits of good nutritional status, exclusive breastfeeding, and complete immunization. Therefore, education regarding the dangers of secondhand smoke exposure and smoking cessation within the household is essential for preventing recurrent bronchopneumonia in children.